Exemplification of Sensitive Words for People with Disabilities in Monolingual English Learner’s Dictionaries - Li, Meimei (Lexikos, 2025)
This paper investigates how sensitive words related to people with disabilities are exemplified in the "Big Five" monolingual English learner’s dictionaries. The findings show that learner’s dictionaries tend to be cautious in exemplifying such terms, with notable differences in the number of words exemplified and examples provided, as well as in the inclusion of additional examples. Despite these variations, the "Big Five" consistently offer phrase and sentence examples for sensitive words that serve both decoding and encoding purposes. The analysis reveals that the exemplification of sensitive words is influenced by factors such as part-of-speech, attitude labelling, and word currency. In general, adjectival forms of sensitive words are more likely to be exemplified than their nominal counterparts. Sensitive words that remain in current use tend to have higher exemplification rates than those considered old-fashioned. Neutral or euphemistic expressions are more frequently illustrated with examples than terms that carry negative connotations. This paper argues for broader exemplification of sensitive words, particularly neutral and euphemistic ones, and recommends optimising the presentation and the quality of additional examples. Keywords: Big Five, exemplification, sensitive words, people with disabilities, inclusive language